Electrical conductivity and optical properties of ZnO nanostructured thin film - Caglar, Mujdat; Ilican, Saliha; Caglar, Yasemin; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2009)
The electrical conductivity, structural and optical properties of ZnO nanostructured semiconductor thin film prepared by sol-gel spin coating method have been investigated. The X-ray diffraction result indicates that the ZnO film has the polycrystalline nature with average grain size of 28 nm. The optical transmittance spectrum indicates the average transmittance higher than 90% in visible region. The optical band gap, Urbach energy and optical constants (refractive index, extinction coefficient, real and imaginary parts of the dielectric constant) of the film were determined. The electrical conductivity of the film dependence of temperature was measured to identify the dominant conductivity mechanism. The conductivity mechanism of the film is the thermally activated band conduction. The electrical conductivity and optical results revealed that the ZnO film is an n-type nanostructured semiconductor with a direct band gap of about 3.30 eV at room temperature. (C) 2008 Elsevier B. V. All rights reserved.
Keywords: ZnO; Nanostructured thin film; Sol-gel spin coating; Optical constants